Intensity of anticoagulation and survival in patients hospitalized with COVID-19 pneumonia. Issue 196 (December 2020) - Hsu, Andrew; Liu, Yuchen; Zayac, Adam S.; Olszewski, Adam J.; Reagan, John L.
Abstract: Background: SARS-CoV-2 infection has noted derangements in coagulation markers along with significant thrombotic complications. Post-mortem examinations show severe endothelial injury and widespread thrombotic microangiopathy in the pulmonary vasculature. Early reports describing the use of prophylactic anticoagulation demonstrated improved survival, leading to the adoption of prophylactic and therapeutic anticoagulation guided by D-dimer levels. The clinical usefulness of D-dimer values, trends, and more intensive anticoagulation remains an area of clinical interest. Objectives: Assess the outcomes and laboratory trends in COVID-19 patients stratified by intensity of anticoagulation at time of admission. Patients and methods: Retrospectively review the differences in clinical outcomes and laboratory trends in patients hospitalized with COVID-19 in the Lifespan Health System. Results: Between 27 February and 24 April 2020, 468 patients were hospitalized. Initial use of high-intensity thromboprophylaxis was associated with improved 30-day mortality (adjusted RR 0.26; 95% confidence interval [CI], 0.07–0.97; p = 0.045) without a significant increased rate of bleeding ( p = 0.11). In severe COVID-19, D-dimer significantly increased during hospitalization with standard thromboprophylaxis ( p < 0.001) but remained stable or decreased with high-intensity prophylaxis or therapeutic anticoagulation. Conclusion: Patients who received high-intensity prophylactic anticoagulation had a downtrend in D-dimer levels and improved 30-day mortality. This suggests a role in anticoagulation in mitigating adverse outcomes associated with COVID-19; however, further randomized, prospective studies are needed. Highlights: High-intensity prophylaxis was associated with improved 30-day mortality High-intensity prophylaxis includes LMWH 40 mg twice daily or unfractionated heparin 7500 units subcutaneous thrice daily. In severe COVID-19, D-dimer significantly increased during hospitalization with standard prophylaxis. In severe COVID-19, D-dimer was stable or decreased with high-intensity prophylaxis or therapeutic anticoagulation. In severe COVID-19, high-intensity prophylaxis or therapeutic anticoagulation did not lead to increased bleeding.